PELESAPAN DAN PENGGANTIAN BUNYI BAHASA ARAB - Anshari Nasution, Ahmad Sayuti (Sunan Kalijaga State Islamic University Yogyakarta, 2015)
The objects of this research are the forms of ellipsis and sound substitution, which occur in Arabic. Those are fuṣÊa Arabic which belong to Egyptian and Saudi Arabian dialects. This research will benefit those who learn and teach Arabic as well as the researcher of Arabic language. As a library research, the data was taken from books, journals, and websites. Subtitution and ellipsis may happen for the purpose of making the sound expression easier to be pronounced, e.g qaf becomes hamzah, jim becomes gain in Egyptian dialect or qaf becomes gain, żal becomes dal in Saudi Arabian dialect. The subtitution and ellipsis also occure with the purpose of simplification as what happens in he removal of ta ta’nis and ta’marbuṭoh.